Characterization of calcium phosphate bioceramic from Paphia undulata shells - Nur Farahiyah, Mohammad; Muhammad Hariz, Muhammed; Zulkarnay, Zakaria; Azian Azamimi, Abdullah; Intan Shafinaz, Mohammad (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/